Hippocrates: Philosophy and Medicine - Ilham Ibnou Zahir (European Scientific Journal, ESJ, 2016)
It is widely acknowledged that modern ‘scientific medicine’ is in crisis. Roy Porter in his magisterial book, The Greatest Benefit to Mankind, points out that ‘these are strange times, when we are healthier than ever but more anxious about our health. According to all the standards benchmarks, we have never had it so healthy.’ (Porter, 1997). This crisis has many aspects and may be explained by modern Western indifference to a holistic and Classical view of ‘health’ and the ‘body’ in favour of a stimulating and progressive medicine driven more by its ‘scientific’ projects to produce a ‘mechanical’ model of the workings of the body. This paper will look into the historical and conceptual meaning of ‘health’, the ‘body’ and the relationship between philosophy and medicine when they were first dealt with and reflected upon by the ancient father of medicine, namely, Hippocrates. The latter was the first European ‘doctor’ to have aimed at seriously putting medicine within the realm of a ‘scientific’ domain, one which denies its important link to philosophy.